The deaf history reader - Van Cleve, John V. (Washington, DC : Gallaudet University Press, 2007)
Van Cleve, who taught history at Gallaudet U. (Washington, DC), the only liberal arts college for the deaf and hard of hearing, introduces nine illustrated essays that challenge stereotypes by former students and others associated with the deaf community. They provide historical perspectives on deaf identity and education in the US, and call for broader scholarship on issues of importance to the deaf community. For example, one author weighs Alexander Graham Bell's mixed legacy as a eugenicist who nonetheless supported reproductive rights for the deaf.
Genesis of a community : the American deaf experience in the seventeenth and eighteenth centuries / Harry G. Lang -- Hearing with the eye : the rise of deaf education in the United States / Barry A. Crouch and Brian H. Greenwald -- Origins of the American deaf-world : assimilating and differentiating societies and their relation to genetic patterning / Harlan Lane, Richard C. Pillard, and Mary French -- Mary Ann Walworth Booth / Jill Hendricks Porco -- A tale of two schools : the Indiana Institution and the Evansville Day School, 1879-1912 / Michael Reis -- The academic integration of deaf children : a historical perspective / John Vickrey Van Cleve -- Taking stock : Alexander Graham Bell and eugenics, 1883-1922 / Brian H. Greenwald -- Deaf autonomy and deaf dependence : the early years of the Pennsylvania Society for the Advancement of the Deaf / Reginald Boyd and John Vickrey Van Cleve -- The Chicago Mission for the Deaf / Kent R. Olney.
Includes bibliographical references and index.
Keywords: Deaf people -- United States -- History; Deaf -- Education -- United States -- History